Resurfacing of hand injury with groin flap: an analysis of thirty four cases (Bangladesh Medical Journal, 2014)
Hand injuries are prevalent among the young adult and middle aged active people specially who are engaged with machinery works. Hand performs the unique and essential mechanical function and for fulfillment of this function it is imperative to provide good soft tissue coverage with sensibility. Skin grafting causes wound contraction and result in gliding of tendon directly under skin and is also unable to provide sensibility. Though cutting and slicing injury can be closed directly, crushing, degloving and avulsion injury needs coverage with a flap. Free flap require highly skilled microvascular anastomoting technique and needs expertise. Pedicle flap are suitable for this purpose where facilities for free flap transfer are not available. This prospective observational study which was done in National Institute of Traumatology and Orthopadic Rehabilitation during the period from January 2000 to december 2001 involving thirty four patients with a age range of 15-50 yrs who sustained hand injury from machinery injury, road traffic accident and electric burn.The patients were followed up at 4th (week), 6th (week), 8th (week), 16th and 20th week. Majority of patient are male. 58.82% of patient had suffered from machinery injury and 23.52% of patient had suffered from road traffic accident. During resurfacing of hand injuries, 58.82% of patient needed a flap length between 15 to 17 cm and rest of the patient (41.16%) requires flap length below 15 cm.Among all patients, 70.6% required 7 cm to 10 cm wide flap and rest of the patient between 5 cm to 7 cm. About 86% of patients had no loss of flap, 10.71% had marginal distal flap loss, 3.57% patient had distal flap loss up to 5% and no patient had distal flap loss >5%. Functional out come in terms of Eating, drinking, dressing,washing, writing were satisfactory in all cases except only one patient who developed stiffness of hand which was 3.58% of total patient. Functional outcome were evaluated in terms of eating, drinking, dressing, washing, writing and other purposeful movement; and also in terms of joint movement, power grip and pinching. All patient regained full range of movement except one patient who had deficit of finger movement. In conclusion groin flap can be a better choice for resurfacing the hand injury with acceptable results. This study recommends the use of groin flap as routine choice for resurfacing larger hand injuries. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21372 Bangladesh Med J. 2014 January; 43 (1): 21-25